Pengaruh Kompensasi Dan Locus Of Control Terhadap Kedisiplinan Karyawan Melalui Kepuasan Kerja - Eka Kurniawati (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2022)
This study aims to analyze the direct effect of compensation and locus of control on employee discipline and the indirect effect of compensation and locus of control on employee discipline through job satisfaction. This study uses a quantitative approach and data analysis techniques use statistics with path analysis techniques (path analysis). The data collection technique used saturated samples with the object of research at YPI Miftahul Huda Papar, Kediri Regency with 45 employees as samples in the study. The results showed (1) compensation has a significant positive direct effect on employee discipline, (2) locus of control has a significant positive direct effect on employee discipline, (3) compensation has a significant positive indirect effect on employee discipline through job satisfaction, (4) locus of control has a significant positive indirect effect on employee discipline through job satisfaction. Suggestions for further research are to develop this research in a different place by adding other factors that can increase employee discipline.